Das Klein-Klein der Arbeit: die Notizführung des Historikers François Louis Ganshof - Trüper Henning (Österreichische Zeitschrift für Geschichtswissenschaften, 2007)
The Belgian mediaevalist François Louis Ganshof (1895–1980) was in the habit of approaching his research topics with the help of large numbers of small slips of paper. The present examination explores his note taking practice in detail, and from different angles. The aim is to show, within the limits of a case study, how strongly material, methods, practice, and concepts were intertwined, and how different tradi- tions and customs were interwoven in Ganshof’s everyday work. The examination of this complex state of affairs can help broaden our perspective on how historical knowledge is produced and suggests that this production must itself be seen as the result of contingent, historical constellations.